Role of renewable energy and globalization on ecological footprint in the USA: implications for environmental sustainability - Usman, Ojonugwa; Akadiri, Seyi Saint; Adeshola, Ibrahim (Springer Heidelberg, 2020)
The role of renewable energy and globalization on ecological footprint is investigated in the USA by controlling for the effects of financial development and real output using quarterly data from 1985:Q1 to 2014:Q4. We apply the minimum Lagrange multiplier unit root test, multiple structural break cointegration test, and autoregressive distributed lag (ARDL) estimation approach. The empirical evidence suggests that, in the long run, renewable energy and real output exert negative pressure on ecological footprint while financial development and globalization exert positive pressure on ecological footprint. The short-run results indicate that renewable energy, financial development, real output, and globalization are positively linked to ecological footprint. The vector error correction model Granger causality results, in the long run, divulge that ecological footprint, consumption of renewable energy, real output, and globalization Granger-cause financial development while ecological footprint, renewable energy, financial development, and globalization Granger-cause real output. The results also show that, in the short run, renewable energy and globalization cause ecological footprint and real output causes renewable energy, while renewable energy causes globalization. The finding also reveals that the causality between real output and globalization, as well as globalization and financial development, is bidirectional. Therefore, our findings provide insights for policymakers to consider consumption of renewable energy as a surest way to mitigate carbon dioxide emissions.
Keywords: Globalization; Renewable energy consumption; Financial development; Maki cointegration test